Faktor-Faktor yang Berhubungan dengan Keberhasilan Pemberian Asi Eksklusif pada Ibu Pekerja di Wilayah Kerja Puskesmas Payangan Kabupaten Gianyar - I Gede Bagus Wikarna Satyabrata Wikarna; Ni Made Hegard Sukmawati; Komang Triyani Kartinawati (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[Factors Associated with the Success of Providing Exclusive Breast Milk to Working Mothers in the Working Area of ​​the Payangan Health Center, Gianyar Regency] Work poses a significant challenge to exclusive breastfeeding, especially as the number of female workers increases annually. The success of only breastfeeding is affected by various things. This study aims to find out what factors are connected to only breastfeeding among moms who work in the Payangan Health Center area, Gianyar Regency. The things they looked at were knowledge, attitude, having the right facilities, how long they work, support from their husbands, and help from healthcare workers. The study used a method where they observed and analyzed data from 91 working mothers. They collected information using questionnaires and g-form media through convenient sampling. They studied the data using simple and comparative analyses like chi-square and Fisher exact test. About 71.4% of working moms did only breastfeeding. The results showed that factors like knowledge, attitude, having the right facilities, work duration, and help from healthcare workers (p<0.05) were related to the success exclusive breastfeeding. However, there wasn't a significants connection betweens husband support with the success exclusive breastfeeding among working mothers (p>0.05). Health workers can play a pivotal role by optimizing the maternity leave period for health promotion and providing education about exclusive breastfeeding. Equipped with adequate knowledge and support, working mothers can better sustain their exclusive breastfeeding journey when they return to work.